The development of ocean governance for marine environment protection: Current legal system in Taiwan - Shih, Yi-Che; Chen, Wei Chung; Chen, Tai-An Peter; Chang, Chih-wei (Frontiers in Marine Science, 2023)
Taiwan establishes Ocean Affairs Council (OAC) in 2018. Ocean governance has reached a new milestone. In 2019, the Ocean Basic Act was enacted. In 2020, the National Ocean Policy White Paper was published, meaning that Taiwan has specialized ocean authorities, regulations, enforcement units, and relevant mechanisms and policies. The Ocean Conservation Administration (OCA) is also responsible for marine environmental protection and conservation. To ensure good ocean governance, maintain marine resources, and protect the environment, the OCA has recently drafted the Marine Conservation Act for sustainable development. This article mainly reviews, analyzes, and compares Taiwan’s current marine-related laws and regulations and refers to the laws, policies, and mechanisms of other countries to provide suggestions on marine governance and the ongoing draft of the Marine Conservation Act.